Integration of Spin‐Coated Nanoparticulate‐Based La0.6Sr0.4CoO3–δ Cathodes into Micro‐Solid Oxide Fuel Cell Membranes. Issue 3 (28th March 2013) - Evans, A.; Benel, C.; Darbandi, A. J.; Hahn, H.; Martynczuk, J.; Gauckler, L. J.; Prestat, M.
Abstract Thin cathodes for micro‐solid oxide fuel cells (micro‐SOFCs) are fabricated by spin‐coating a suspension of La0.6Sr0.4CoO3–δ (LSC) nanoparticulates obtained by salt‐assisted spray pyrolysis. The resulting 250 nm thin LSC layers exhibit a three‐dimensional porous microstructure with a grain size of around 45 nm and can be integrated onto free‐standing 3 mol.% yttria‐stabilized‐zirconia (3YSZ) electrolyte membranes with high survival rates. Weakly buckled micro‐SOFC membranes enable a homogeneous distribution of the LSC dispersion on the electrolyte, whereas the steep slopes of strongly buckled membranes do not allow for a perfect LSC coverage. A micro‐SOFC membrane consisting of an LSC cathode on a weakly buckled 3YSZ electrolyte and a sputtered Pt anode has an open‐circuit voltage of 1.05 V and delivers a maximum power density of 12 mW cm–2 at 500 °C.